Natural Environment Strategy Data Disclosure Instruments Study On Palm Oil Companies In Riau Province - Mashur Fadli; Meyzi Heriyanto; Yusmar Yusuf; Isril; Mandataris; M.Y.Tiyas Tinov (CV. Inara, 2021)
The goal of this research is to create and validate the scale. A total of 126 workers from a palm oil plant in Riau province were included in this investigation. Win step program is used to analyze data using the Rasch model. This is supported by research. In the unsatisfactory category, the Cronbach alpha value, which measures the overall interaction between people and items, is included. Furthermore, the importance of person reliability as a measure of the consistency of respondents' responses is categorized as extremely bad. In the meantime, item reliability as a measure of the instrument's quality falls into a distinct category. The standard items' average difficulty level is below the ability level of the palm oil mill's managers. As a result, palm oil mill management readily approves this natural environment plan instrument item.